Miasta Skandynawii w świetle luźnych kartek z podróży Macieja Szukiewicza (Heteroglossia – studia kulturoznawczo-filologiczne, 2025)
This article examines the lesser-known travel writings of Maciej Szukiewicz, a Polish modernist poet and playwright, who visited Scandinavia in 1899 and documented his experiences in the collection From the Land of Fjords and Fells (Z ziemi fiordów i fieldów). The study aims to illuminate Polish-Scandinavian cultural relations at the fin de siècle, with particular emphasis on visual arts and everyday cultural practices. Szukiewicz’s narrative technique – blending objective observation with subjective reflection – creates a multilayered account in which realism intertwines with poetic expression, endowing the text with both documentary value and artistic merit.